Outlining a typology of sports coaching careers: paradigmatic trajectories and ideal career types among high-performance sports coaches - Christensen, M. K. (Sports Coaching Review, 2013)
This paper aims to extend our understanding of sports coaching careers and challenge related stage-based models by outlining and describing a typology of careers in high-performance sports coaching. A constructivist research approach is applied that intends to gain insight into the realities of coaches' careers. Data were drawn from in-depth interviews with 10 Danish high-performance sports coaches. Results identified four classifying features that pave the way for the establishment of a typology consisting of three ideal types: (1) the elite-athlete coach; (2) the academic coach; and (3) the early-starter coach. The findings are theorized through Wenger's concept of paradigmatic pathways and Bourdieu's concept of cultural capital. The study illuminates paradigmatic trajectories and conversions of cultural capital in high-performance sports coaching careers that may act as models for young athletes transitioning into the coaching profession.